HYPERTENSION RESPONSE THROUGH IMPROVING SELF-CARE MANAGEMENT SKILLS IN ELDERLY AGGREGATES WITH HYPERTENSION: TANGGAP HIPERTENSI MELALUI PENINGKATAN KETERAMPILAN MANAJEMEN PERAWATAN DIRI PADA AGREGAT LANSIA HIPERTENSI - Irwina Angelia Silvanasari; Nurul Maurida; Trisna Vitaliati; Achmad Ali Basri; Sulton Wariin (Darmabakti Cendekia: Journal of Community Service and Engagements, 2026)
Background: Hypertension still requires serious and continuous treatment. Hypertension response is a mentoring program carried out as an effort to control blood pressure in the aggregate of the elderly with hypertension. Objective: The objective of this activity is to improve the self-care management behavior of the elderly with hypertension and to control blood pressure. Method: The method of hypertension response activities consists of strengthening the perception of vulnerability, education on diet strategies, physical activity demonstrations, and stress management demonstrations for the target aggregate of elderly with hypertension, which are divided into four activity sessions. The partner in this activity is the Jenggawah Community Health Center. Evaluation was carried out by comparing the pretest and posttest scores of the HSBMQ questionnaire and systolic and diastolic blood pressure. Results: There was an increase in the average self-care management score. The decrease in systolic blood pressure was 19.11 mmHg, and in diastolic blood pressure, 6.79 mmHg. Conclusion: Hypertension response activities were able to improve self-care management and control blood pressure in the elderly with hypertension. The elderly who understand their susceptibility to hypertension, follow a hypertension diet, physical activity recommendations, and stress management will be able to control their hypertension more optimally.